Evaluation of a simple ski jumping model - Schindelwig, K.; Nachbauer, W. (4th International Congress on Science and Skiing, 2007)
INTRODUCT1ON: The influences of in-run and take-off velocities, lift and drag forces during take-off and flight phase as well as weight of the ski jumper and his equipment on the Jump distance were analysed in several Computer simulations (e.g. Ward-Smith, A.J., Clements, D., 1983). These simulations require input Parameters, which are usually not available for world class ski jumpers, e.g. weight or lift and drag as function of the stream direction. Thus in this study a simple model was evaluated without consideration of individual weight and individual lift and drag areas.